Neuronal Signaling Involved in Neuronal Polarization and Growth: Lipid Rafts and Phosphorylation - Igarashi, Michihiro; Honda, Atsuko; Kawasaki, Asami; Nozumi, Motohiro (Frontiers in Molecular Neuroscience, 2020)
Neuronal polarization and growth are developmental processes that occur during neuronal cell differentiation. The molecular signaling mechanisms involved in these events in in vivo mammalian brain remain unclear. In addition, cellular events of the neuronal polarization process within a given neuron are thought to be constituted of many independent intracellular signal transduction pathways (the “tug-of-war” model). However, in vivo results suggest that such pathways should be cooperative with one another among a given group of neurons in a region of brain. Lipid rafts, specific membrane domains with low fluidity, are candidates for the hotspots of such intracellular signaling. Among the signals reported to be involved in polarization, a number are thought to be present or translocated to the lipid rafts in response to extracellular signals. As part of our analysis, we discuss how such these novel molecular mechanisms are combined for effective regulation of neuronal polarization and growth, focusing on the significance of the lipid rafts, including results based on recently introduced methods.